Twin Cities Sports : Games for All Seasons - Anderson, Sheldon R., 1951- (Book collections on Project MUSE., 2020)
"Minneapolis and St. Paul sit on two sides of the upper Mississippi far away from any other major city. For over thirty years on his Minnesota Public Radio show humorist Garrison Keillor conjured up a distinct image of "Lake Wobegon" as a place of bland, cold, colorless Nordic sameness. The state has the reputation of a forbidden land of relentless whiteness. Keillor rarely talked about sports. The colorful and rich history of Twin Cities' sports has often been overlooked. The Twin Cities is one of only five metropolitan areas in the United States that has all of the major league professional sports (including women's basketball and men's soccer), and a university with Division-1 sports. This anthology includes stories of the Minnesota Twins' move from Washington D.C., the world-renowned park system, the five-time NBA champion Minneapolis Lakers, the peculiar Cuban baseball connection to the Twins, and professional football (culminating in the expansion NFL franchise Minnesota Vikings). The book focuses on themes of regional, class, and ethnic identity. One chapter examines the area's highly successful professional wrestling franchise, and its connection to the Slavic community in Northeast Minneapolis. Another chapter examines the rise and fall of the football Gophers, a team that won five national championships in the 1930s, and another in 1960 with the help of African-American players from the South who were banned from playing on white universities there. After the end of Jim Crow, Minnesota football has fallen on very hard times. A chapter on the history of golf also highlights the struggle of African-American and women golfers to play on Twin City courses"--